The Effectiveness of Digital Literacy Indicators in Improving Students' Reading Interest - Idam Ragil Widianto Atmojo; Chumdari Chumdari; Dwi Yuniasih Saputri; Roy Ardiansyah; Ainun Nafisah; Matsuri Matsuri (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to determine the effectiveness of digital literacy indicators in improving students' reading interests. The research method used is quantitative. The samples in this study were the fifth-grade students at SDN Pajang IV, SDN Tegalrejo, SDN 1 Jajar, and SDN Setono, totaling 86 respondents. The data collection technique used is a questionnaire. The data analysis used is SEM (Structural Equation Model) analysis with SmartPLS and SPSS programs. This research was conducted by testing the instrument outside the sample but in one regional population. After that, the instrument was distributed to the research sample. The results of the study revealed that the effectiveness of digital literacy in improving reading interest was 29%. Further research needs to be done to improve elementary school students’ digital literacy and reading interest.